Novel EAAT2 activators improve motor and cognitive impairment in a transgenic model of Huntington’s disease - Bhatnagar, Akanksha; Parmar, Visha; Barbieri, Nicholas; Bearoff, Frank; Elefant, Felice; Kortagere, Sandhya (Frontiers in Behavioral Neuroscience, 2023)
Glutamate excitotoxicity is causal in striatal neurodegeneration underlying motor dysfunction and cognitive deficits in Huntington’s disease (HD). Excitatory amino acid transporter 2 (EAAT2), the predominant glutamate transporter accounting for > 90% of glutamate transport, plays a key role in preventing excitotoxity by clearing excess glutamate from the intrasynaptic cleft. Accordingly, EAAT2 has emerged as a promising therapeutic target for prevention of neuronal excitotoxicity underlying HD and other neurodegenerative diseases. We have previously designed novel EAAT2 positive allosteric modulator GT951, GTS467 and GTS551, with low nanomolar efficacy in glutamate uptake and favorable pharmacokinetic properties. In this study, we test the neuroprotective abilities of these novel EAAT2 activators in vivo using the robust Drosophila HD transgenic model expressing human huntingtin gene with expanded repeats (Htt128Q). All three compounds significantly restored motor function impaired under HD pathology over a wide dose range. Additionally, treatment with all three compounds significantly improved HD-associated olfactory associative learning and short-term memory defects, while GT951 and GTS551 also improved middle-term memory in low-performing group. Similarly, treatment with GT951 and GTS551 partially protected against early mortality observed in our HD model. Further, treatment with all three EAAT2 activators induced epigenetic expression of EAAT2 Drosophila homolog and several cognition-associated genes. Together, these results highlight the efficacy of GT951, GTS467 and GTS551 in treating motor and cognitive impairments under HD pathology and support their development for treatment of HD.